Key determinants of adoption of soil and water conservation measures: A review - KUMAR, SURESH; SINGH, D R; JHA, G K; MONDAL, B; BISWAS, H (The Indian Journal of Agricultural Sciences, 2021)
We synthesized the information on the determinants of soil and water conservation measures to draw the useful insights for policy implications. We found that there are no universally significant factors affecting the adoption of soil and water conservation measures across the regions. Therefore, there is a need for‘location-specific targeted policies’ for increasing uptake of soil and water conservation measures. Factors such as ‘access to extension services’, ‘access to credit’, ‘marketing facilities’, ‘training’ and ‘collective actions’ were found be having a positive impact on adoption of soil and water conservation measures. Broadly, findings suggest that policy makers should focus on the institutional and economic factors for increasing the use of conservation measures.